Obstetric, neonatal and child development outcomes following assisted hatching treatment: a retrospective cohort study. (2nd January 2021) - Shats, Maya; Fenchel, Daphna; Katz, Guy; Haas, Jigal; Machtinger, Ronit; Gat, Itai; Orvieto, Raoul; Kedem, Alon
Abstract: Assisted hatching (AH) involves artificial disruption of the zona pellucida prior to embryo transfer. The purpose of this study is to examine the safety of AH technique and its effect on obstetrical, perinatal and neonatal outcomes and risk of developmental delay. This is a retrospective cohort of ART cycles using laser AH technique. The study group consisted of 120 cases of AH cycles resulting in singleton pregnancies and live births compared with 113 control cases. A current phone questionnaire was conducted to assess child development in the first year of life. AH was not associated with increased risk for all obstetrical and perinatal outcomes examined including PPROM, gestational diabetes, hypertensive diseases of pregnancy, delivery by cesarean section, gestational age at delivery, low birth weight (LBW), preterm birth and neonatal Apgar score ( p >.05). No significant differences were observed between AH and control group in rates and risk of congenital malformations (5.8 vs. 4.4%, respectively, OR 1.33, 95% CI 0.41–4.34) and developmental delay (19.2 vs. 12.8%, respectively, OR 1.62, 95% CI 0.74–3.52). AH did not increase the risk of obstetrical and neonatal complications in singleton pregnancies, including congenital malformations and child developmental delay. AH may therefore be considered a safe method of ART.